2016
DOI: 10.1080/10826084.2016.1188946
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients in Long-Term Opioid Maintenance Treatment

Abstract: The sample as a whole was characterized by stable living conditions, high unemployment, low illicit opiate use, and a high retention rate. Continuation of OMT could enable further treatment of comorbidity and prevent resumption of a drug-dominated lifestyle. But it may well be asked how within the context of OMT further improvements can be achieved, especially with regard to further decrease of alcohol use and the treatment of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
11
0
2
Order By: Relevance
“…Long-term studies of OMT patients have shown the longer the duration of treatment, the more stabilized a patient remains (Appel et al, 2001;Zippel-Schultz et al, 2016). For inpatients, the goal is to complete a distinct course of treatment.…”
Section: Sud Treatment Approachesmentioning
confidence: 99%
“…Long-term studies of OMT patients have shown the longer the duration of treatment, the more stabilized a patient remains (Appel et al, 2001;Zippel-Schultz et al, 2016). For inpatients, the goal is to complete a distinct course of treatment.…”
Section: Sud Treatment Approachesmentioning
confidence: 99%
“…Although substitution treatment makes a substantial contribution to ensuring patients' survival (23), only some 4% of patients per year successfully complete treatment (24)(25)(26). At the same time, there is evidence in the literature of a decline in new cases of opioid-related disorders in Europe (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Für die Mehrheit dieser in chronischen Problemsituationen befindlichen Patienten ist die Substitutionsbehandlung zeitlich nicht limitiert. Nach der PREMOS-Studie gibt es sogar Hinweise, dass Praxen mit einer deutlichen Abstinenzorientierung (einschließlich der Abstinenz vom Substitutionsmittel) schlechtere Behandlungsergebnisse erzielten als die übrigen Praxen [12]. Zudem unterliegen Patienten nach Ende einer Substitution einem erheblich gesteigerten Mortalitätsrisiko im Vergleich zu Patienten, die in Substitution verbleiben [15].…”
Section: Analyse Der Studienbeenderunclassified